Computation of H ∞ controllers for infinite dimensional plants using numerical linear algebra1. Issue 2 (14th February 2012) - Özbay, H.; Chu, Eric; Lin, Wen‐wei; Reichel, Lothar
SUMMARY The mixed sensitivity minimization problem is revisited for a class of single‐input‐single‐output unstable infinite dimensional plants with low order weights. It is shown that H ∞ controllers can be computed from the singularity conditions of a parameterized matrix whose dimension is the same as the order of the sensitivity weight. The result is applied to the design of H ∞ controllers with integral action. Connections with the so‐called Hamiltonian approach are also established. Copyright © 2012 John Wiley & Sons, Ltd.